The Role of the MUI Fatwa Commission in Providing Solutions to Religious and Social Problems - Shofi Hanifatunnisa; Asep Gunawan; Muhamad Taufiqur Rahman; Shofi Ulul Musyafa’ah (LPPM UIKA Bogor, 2024)
The development of science and technology affects people's lives, including in the field of law, especially for Muslim communities. Although they have legal guidance in the Qur'an and Hadith, the need for clerical guidance remains important. This research uses a qualitative method and literature study approach to understand the role of the Fatwa Commission in the Indonesian Ulema Council (MUI). Data was obtained from scholarly literature, with the aim of understanding existing information and identifying knowledge gaps that can be filled. MUI, through its fatwa commission, provides guidance on Islamic law using the ijtihad method. The fatwa commission has a key role in providing legal guidance that is relevant and applicable to the lives of Muslims in Indonesia.